2022
DOI: 10.1186/s43055-022-00698-z
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging findings in hospitalized patients with COVID-19

Abstract: Background Variable neuroimaging findings have been reported in patients with coronavirus disease 2019 (COVID-19). In addition to respiratory symptoms, many neurologic manifestations of COVID-19 are increasingly reported and variable neuroimaging findings have been observed in patients with COVID-19. Our aim was to describe findings observed in hospitalized patients with COVID-19, presenting with acute neurologic manifestations and undergoing computed tomography (CT) or magnetic resonance imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Agreeing with Saleh et al [ 16 ], and Abdelzaher et al [ 17 ], the ischemic infarctions were the most common neurovascular complications and a disturbed level of consciousness was the most common clinical presentation. Meanwhile, the presence of hemorrhagic insults and vasculitis was infrequent.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Agreeing with Saleh et al [ 16 ], and Abdelzaher et al [ 17 ], the ischemic infarctions were the most common neurovascular complications and a disturbed level of consciousness was the most common clinical presentation. Meanwhile, the presence of hemorrhagic insults and vasculitis was infrequent.…”
Section: Discussionmentioning
confidence: 69%
“…The incidence of thromboembolic complications was 124/1245 (10%) which was near to this study (8%). Saleh et al [ 16 ], and Abdelzaher et al [ 17 ] studied only the vascular and non-vascular neurological complications of COVID-19 infection. The former included 70 patients over 14 months till July 2021 and the latter included 135 patients over six months till December 2020.…”
Section: Discussionmentioning
confidence: 99%
“…This finding corroborates the observations of previous studies [ 13 , 127 , 128 ]. Other neuroimaging findings included ischaemic or haemorrhagic stroke [ 37 , 56 , 81 ], cerebral venous sinus thrombosis [ 21 , 88 , 105 ], and acute or subacute infarction [ 54 , 68 , 107 ]. Of note, Ntaios et al demonstrated that patients with ischaemic stroke related to COVID-19 had worse functional outcomes and higher mortality than patients with ischaemic stroke and without COVID-19 [ 129 ].…”
Section: Discussionmentioning
confidence: 99%